Penerimaan Program Pekarangan Pangan Lestari (P2L) pada KWT Jaya Kerti Lestari dalam Menjaga Ketahanan Pangan Rumahtangga di Desa Rendang Kecamatan Rendang, Kabupaten Karangasem - ASTITI, NI WAYAN SRI; PARINING, NYOMAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.2, Desember 2023, 2023)
Acceptance of the Sustainable Food Yard Program (P2L) at KWT Jaya Kerti Lestari in Maintaining Household Food Security in Rendang Village Rendang District, Karangasem Regency.  This study aims to create an acceptance model of the P2L Program in maintaining the resilience of community households, and knowing the characteristics of respondents. The research location is in KWT Jaya Kerti Lestari, Rendang Village, Rendang District, Karangasem. Respondents were determined by census as many as 40 people who were members of KWT Jaya Kerti Lestari. Data collection with structured and in-depth interviews and documentation. Data analysis was carried out qualitatively descriptive and SEM analysis methods. The results showed that the characteristics of respondents include, the average age of 55.09 years, the average education of 6.05 years equivalent to graduating from elementary school, the average household of 3 people, the average ownership of yard land covering an area of 4.80 acres, predominantly having the main job of farmers and their side as traders. The results also showed that the level of knowledge of KWT members towards the P2L program was high (score 72.27%), the attitude of KWT members towards the P2L program was classified as agreeable (score 77.63%), and the level of application of KWT members to the P2L program was high (score 77.58%). P2L program acceptance is high with a score of 76.95%. The acceptance of the P2L program is seen from the welfare indicators of KWT members which are classified as high (score 79%), acceptance of innovation (score 67%) in the Medium category and Cooperation of group members in carrying out P2L program activities is high with a score of 82.20%. Furthermore, to see the acceptance of P2L programs in maintaining household food security, it will be analyzed with SEM-PLS. Through the results of the analysis, the acceptance model of the P2L Program is largely determined by the implementation of the P2L program which is influenced by cooperation with a t-stat value of 3.104 (above 1.96) and a p-value of 0.002.